Self-Reported Medication Adherence Measured With Morisky Medication Adherence Scales and Its Determinants in Hypertensive Patients Aged ≥60 Years: A Systematic Review and Meta-Analysis - Bartosz Uchmanowicz; Ewa A. Jankowska; Izabella Uchmanowicz; Donald E. Morisky (Frontiers Media S.A., 2019)
Background: The aim of this systematic review and meta-analysis was to estimate medication adherence in hypertensive patients aged ≥60 years and to explore potential determinants of adherence with antihypertensive treatment in this age group.Methods: A systematic search of the PubMed, Scopus, and Google Scholar using the Cochrane guidelines was performed. The analysis included articles published between 1 January 2000 and 30 June 2018. The patients were considered adherent if they scored ≥6 pts. on the Morisky Medication Adherence Scale (MMAS-8) or ≥3 pts. on the Morisky Green Levine Medication Adherence Scale (MGL). If available, also odds ratios (OR) with 95% confidence intervals (95% CI) for determinants of medication adherence were recorded.Results: Thirteen studies including a total of 5,247 patients were available for the meta-analysis. The pooled percentage of adherence was 68.86% (95% CI: 57.80-79.92%). Subgroup analysis did not demonstrate a significant difference in the adherence measured with the MMAS-8 and the MGL (68.31 vs. 70.39%, P = 0.773). The adherence of patients from Western countries (Europe, United States) turned out to be significantly higher than in other patients (83.87 vs. 54.30%, P = 0.004). The significant determinants of better adherence identified in more than one study were older age, retirement/unemployment, duration of hypertension >10 years, and a lower number of prescribed drugs.Conclusion: Medication adherence in the oldest old hypertensive patients seems to be higher than in younger persons. Adherence in older persons was associated with age, socioeconomic status, and therapy-related factors.